Dads make a difference: an exploratory study of paternal support for breastfeeding in Perth, Western Australia - Howat Peter; Hauck Yvonne L; Maycock Bruce; Tohotoa Jenny; Burns Sharyn; Binns Colin W (BMC, 2009)
Abstract Background The ability to breastfeed and continue the practice requires dedication, commitment, persistence and support. Mothers often need to overcome many obstacles to successfully breastfeed their babies and maintain their balance of home, family and work commitments. Evidence suggests that fathers want to be involved and be part of the parenthood process, including infant feeding. The role transition from couple to family poses challenges to both parents. Sharing the experience of childbirth and supporting each other in the subsequent infant feeding practices is one of those challenges. Methods A qualitative exploratory design was chosen to identify parents' perceptions of what constitutes support for breastfeeding, particularly focusing upon paternal support. Focus groups were conducted with mothers and a focus group, interviews and an online survey were developed for fathers. Thematic analysis was used to identify the main themes. Results From a total of 76 participants, the major theme emerging from mothers' data identified that "Dads do make a difference". Three sub-themes included: Anticipating needs and getting the job done; Encouragement to do your best; and Paternal determination and commitment, associated with effective partner support. "Wanting to be involved" was identified from fathers' data as the major theme around their needs. Three sub-themes included: Wanting more information; Learning the role; and Being an advocate. Conclusion Sharing the experience of childbirth and supporting each other in the subsequent infant feeding practices was perceived as the best outcome for the majority of new mothers and fathers. Paternal emotional, practical and physical supports were identified as important factors to promote successful breastfeeding and to enrich the experience for the mother and subsequently the father. Trail Regristration Australia and New Zealand Clinical Trials Registry: ACTRN12609000667213.